Curing the sick man: The German labour market on the way to good health? - Ulrich Walwei (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
In 1999, 'The Economist' referred to Germany with the meaningful headline 'The sick man of the euro'. 15 years later, the world is talking about the 'German Labour Market Miracle'. In the first part, this paper describes the characteristics of the traditional German labour market, the resulting situation, and the problems which had to be tackled. In the process of curing Germany's problems, the fundamental reforms of the Schröder-administration played a significant role by bringing more flexibility to the labour market. In a second part, the report outlines current difficulties of the German labour market such as persistent long term unemployment. It also tries to find answers to the question whether the German labour market is in a healthy state now. Furthermore, the author presents an outlook on challenges the country may face in the near future.
Keywords: 330